(3GdeaGgje GdMOjKI aj CfXeI GdeYdheGJ GdMGShHjIs - (3YeGO YHO GdhgGH(B, (3GdUHGZs ((3YeGf(B:s (3ecJHI OGQ GdKbGaI ddfTQ(B,s, 1997)
(3GdeaGgje GdYGeI dCfXeI GdeYdheGJ GdMGShHjI,Md GdeTGcd HhGSWI fXGe GdeYdheGJ GdMGShHj,GdJNWjW GdGSJQGJjLj dfXGe GdeYdheGJ GdMGShHj,JWhjQ fXGe GdeYdheGJ GdMGShHj,JMdjd fXGe GdeYdheGJ GdMGShHj,GdJUeje GdeaUd dfXGe GdeYdheGJ GdMGShHj(B:(3GdfeGPL hGdGLQGAGJ,GdJUeje GdeaUd dfXGe GdeYdheGJ GdMGShHj GdGJUGdGJ,JWhjQ bGYOI GdHjGfGJ hGYJHGQGJ GdJUeje,HfGA GdedaGJ,Jbhje hJHQjQ GdfXGeJfUjH fXGe GdeYdheGJ GdMGShHjs
Keywords: (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s